ANALISIS SALURAN PEMASARAN DAN MARGIN PEMASARAN BIJI PALA DI DESA BELENGANG KECAMATAN MANGANITU KABUPATEN KEPULAUAN SANGIHE - Takasihaeng, Marfanuel; Rengkung, Leonardus Ricky; Lolowang, Tommy Ferdy (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the form of marketing channels and marketing margins of nutmeg in Belengang Village, Manganitu District, Sangihe Islands Regency. The data used in this study are primary and secondary data. Sampling of farmers is done by simple random sampling method and for traders as marketing institutions using the snowball sampling method. The number of farmer samples obtained were 30 farmers. The data is presented in tabular form and analyzed descriptively. The results show that there are 3 forms of marketing channels which are divided into 5 marketing channels: (1) marketing channel level 1: farmers - traders in Tanjung Lelepu district - exporters, (2) marketing channels at 2 levels: farmers - traders in the central district of Tahuna City – traders in the province of Manado City – exporters (b) farmers – traders in Pasar Tamako sub-district – traders in Tanjung Lelepu district – exporters, (3) 3 level marketing channels: (a) farmers – traders in Belengang village – collectors traders in the city center district Tahuna – traders in the province of Manado City – exporters (b) farmers – traders in Pasar Lebo sub-district – traders in the central district of Tahuna City – traders in the province of Manado City – exporters. The highest marketing margin is in marketing channel I with a total margin of Rp 40.800/Kg.